Ag-Coated Cu/Polylactic Acid Composite Filament for Lithium and Sodium-Ion Battery Current Collector Three-Dimensional Printing via Thermoplastic Material Extrusion - Maurel, Alexis; Kim, Hyeonseok; Russo, Roberto; Grugeon, Sylvie; Armand, Michel; Panier, Stephane; Dupont, Loic (Frontiers in Energy Research, 2021)
This paper focuses on the development of a polylactic acid (PLA)-based thermoplastic composite filament, for its use, once 3D-printed via Thermoplastic Material Extrusion (TME), as current collector at the negative electrode side of a lithium-ion battery or sodium-ion battery. A high electronic conductivity is achieved through the introduction of Ag coated-Cu charges, while appropriate mechanical performances to allow printability were maintained through the incorporation of poly(ethylene glycol) dimethyl ether average Mn∼500 (PEGDME500) as plasticizer, into the PLA polymer matrix. Herein, thermal, electrical, morphological, electrochemical and printability characteristics are discussed thoroughly. While Ag-Li alloy formation is reported at 0.1 V upon cycling, its use with active materials such as Li4Ti5O12 (LTO) or Li2-terephtalate (Li2TP) operating at a plateau at higher potential, is demonstrated. Furthermore, its ability to be used with negative electrode active material of a sodium-ion battery technology in a wide range of potential window is demonstrated.